2021
DOI: 10.3390/en14051309
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Short Carbon-Chain Alcohol (Ethanol and 1-Propanol)/Diesel Fuel Blends over Diesel Engine Emissions

Abstract: Oxygenated fuels, in this case short carbon-chain alcohols, have been investigated as alternative fuels to power compression ignition engines. A major advantage of short-chain alcohols is that they can be produced from renewable resources, i.e., cultivated commodities or biomass-based biorefineries. However, before entering the market, the effects of short-chain alcohols on engine performance, exhaust emissions, noise and sound quality need to be understood. This work sheds light on the relationship between th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 42 publications
0
21
0
Order By: Relevance
“…Table 1. Physiochemical characteristics of diesel fuel and commonly used alcohols to fuel diesel engines [12,13]. 1.…”
Section: Alcoholsmentioning
confidence: 99%
See 2 more Smart Citations
“…Table 1. Physiochemical characteristics of diesel fuel and commonly used alcohols to fuel diesel engines [12,13]. 1.…”
Section: Alcoholsmentioning
confidence: 99%
“…The author stated that the addition of butanol to diesel fuel increased engine vibration, while combustion noise was 2-3 dB(A) above that of straight diesel fuel. Redel-Macías et al [13] analyzed the influence of adding propanol and ethanol to diesel fuel, in terms of noise. The authors found that the higher the percentage of alcohol in the blend, the higher the engine noise.…”
Section: Noise Emissionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, alcoholic mixtures resulting from bioprocesses can be effectively used as fuel substitutes or additives with a view to increasing the octane number, ensuring a better combustion, reducing harmful exhaust pipe emissions, and thus protecting the environment. Indeed, light alcohols are directly used as a blendstock with gasoline in many countries such as Brazil, Europe and the USA [1]. Among them, ethanol and butanol can be mentioned, which have been proven to reduce life-cycle greenhouse gas emissions when produced from biomass and waste feedstock [2], though some problems are encountered when operating these processes [3,4], and high costs are involved in the downstream product recovery [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…It is also important to highlight that the use of isooctane as an entrainer can be extremely beneficial in the case of 2-propanol dehydration: traces of such an entrainer do not pose a problem within the recovered dehydrated alcoholic product with a view to its subsequent use as a fuel. [27] New simulation method for three-phase distillation using a modified phase-stability analysis Luyben [24] Process simulation Pienaar [30] Process simulation cyclohexane Gomis et al [45] VLE and VLLE data toluene Gomis et al [62] VLE and VLLE data Zhao et al [31] Process simulation isooctane or 2,2,4-trimethylpentane Cairns and Furzer [27] New simulation method for three-phase distillation using a modified phase-stability analysis Font et al [28] VLE and VLLE data Simulation method 1 Wang et al [26] Experiment using a laboratory-scale sieve plate distillation column; dynamic simulation Chien et al [21] Dynamics and control of a HAD column…”
Section: Introductionmentioning
confidence: 99%